Comparative analysis of neuroinvasion by Japanese encephalitis virulent and vaccine viral strains in an in vitro model of human blood-brain barrier. - Cécile Khou (Public Library of Science (PLoS), 2021)
Japanese encephalitis virus (JEV) is the major cause of viral encephalitis in South East Asia. It has been suggested that, as a consequence of the inflammatory process during JEV infection, there is disruption of the blood-brain barrier (BBB) tight junctions that in turn allows the virus access to the central nervous system (CNS). However, what happens at early times of JEV contact with the BBB is poorly understood. In the present work, we evaluated the ability of both a virulent and a vaccine strain of JEV (JEV RP9 and SA14-14-2, respectively) to cross an in vitro human BBB model. Using this system, we demonstrated that both JEV RP9 and SA14-14-2 are able to cross the BBB without disrupting it at early times post viral addition. Furthermore, we find that almost 10 times more RP9 infectious particles than SA14-14 cross the model BBB, indicating this BBB model discriminates between the virulent RP9 and the vaccine SA14-14-2 strains of JEV. Beyond contributing to the understanding of early events in JEV neuroinvasion, we demonstrate this in vitro BBB model can be used as a system to study the viral determinants of JEV neuroinvasiveness and the molecular mechanisms by which this flavivirus crosses the BBB during early times of neuroinvasion.